Impacts of Mississippi River diversions on salinity gradients in a deltaic Louisiana estuary: Ecological and management implications - Das, Anindita; Justic, Dubravko; Inoue, Masamichi; Hoda, Asif; Huang, Haosheng; Park, Dongho (Academic Press, 2012)

(untitled)
Large-scale river diversions on the lower Mississippi River are considered to be an important component of wetland restoration efforts in coastal Louisiana. Diversions are used primarily for salinity control but increasingly proposed also as a major way to deliver sediments and nutrients to coastal wetlands impacted by the construction of flood control levees. We used a coupled hydrology–hydrodynamics model of the Barataria estuary, a site of the Davis Pond Diversion – the world's largest river diversion project, to examine salinity variations under different diversion discharge scenarios. Discharge scenarios were selected based on actual freshwater discharges in different years and management alternatives that included a scenario with several new diversions. The model results indicate that river diversions strongly affect salinities only in the middle section of the Barataria estuary. The upper parts of the estuary are fresh most of the time and so the excess fresh water from river diversions has only a minor impact on salinity in this region. Also, the Davis Pond diversion has little impact on salinities in the coastal section of the estuary because of strong marine influence in this area adjacent to the Gulf of Mexico. Interestingly, the predicted salinity differences between different model scenarios can be as high as 10 in some months and places. These differences can be biologically significant depending on the salinity tolerance of different species and could cause a shift in community composition within the affected region.